Smoking and socio‐economic status may affect myasthenia gravis. Issue 3 (31st August 2012) - Maniaol, A. H.; Boldingh, M.; Brunborg, C.; Harbo, H. F.; Tallaksen, C. M. E.
Abstract : Background and purpose: The influence of environmental factors in myasthenia gravis (MG) is unknown. The aim of this cross‐sectional population‐based study was to investigate if smoking and socio‐economic status (SES) were associated with MG in the Norwegian population. Methods: Subjects were 491 MG patients identified in Norway at the time of the study (point prevalence 12.7/100 000). A questionnaire covering smoking habits and markers of SES (education and occupation) was mailed to all patients. Population data were obtained from Statistics Norway. Results: A total of 375 (76.6%) patients completed the questionnaire (236 women, mean age 59 ± 18 years), of which 193 reported to be early onset MG (EOMG, onset ≤40 years, 155 women). Compared with the general population, current smoking was more prevalent amongst MG patients [risk ratio (RR) 1.5; 95% confidence interval (CI) 1.1–1.9], most of whom had EOMG. Female MG patients had higher education compared with the general population (RR 4.5; 95% CI 3.2–6.2). Male MG patients were similar to the general population regarding both education and occupation, except for a subset of late onset MG who had shorter education (RR 1.9; 95% CI 1.1–3.2) and had worked in crafts and related trades. About half of working age MG patients received disability pension, a finding significantly related to low educational level and a more severe disease course ( P < 0.001). Conclusion: This is the first report indicating that smoking and SES may affect MG. Further studies investigating their role as potential risk factors are warranted.